Immigrants and the space of national minorities in contemporary Europe = Imigranci a przestrzeń mniejszości narodowych we współczesnej Europie - Chodubski, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study indicates that contemporary migration movements of the population in Europe are typical of the cultural and civilizational development of the world. eir main cause involves the problem of meeting needs, especially in terms of money and living. The institutions of the European Union, which stress the guarantee of the rights of a human and a citizen, attach significant importance to them.
Keywords: migration; European space; national minorities; European Union; cultural and civilizational transformation; migracja; przestrzeń europejska; mniejszości narodowe; Unia Europejska; przemiany kulturowo-cywilizacyjne